Uv-curing edge banding process based on chemically glued reinforced house- hold panel edge banding
Patent Information
- Application Number
- CN202610788866.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-13
AI Technical Summary
其一,热熔胶含有甲醛、挥发性有机化合物等有害成分,在家具使用过程中持续释放,污染室内环境,无法满足高端环保家具、儿童家具的健康使用要求;
1、本发明中板材与封边层通过共价键结合,剥离强度较传统物理吸附提升3-5倍,耐水浸泡剥离率降至2%以下,实现长期稳定的牢固粘接,显著降低脱落风险。使用无甲醛UV树脂,环保健康,当结合梯度模量结构时,化学锚固的弹性缓冲层可随木材干缩湿胀同步变形,应力被有效吸收,硬质面层不开裂,封边寿命大幅延长。
Smart Images

Figure CN122896258A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of board processing technology, specifically to a UV-cured edge banding process for chemically bonded reinforced edge banding of home furnishing boards. Background Technology
[0002] Currently, edge banding processing for panel furniture generally adopts the traditional process of using edge banding strips and hot melt adhesive. This process involves using hot melt adhesive to fix edge banding strips such as PVC, ABS, and solid wood veneer to the side of the board, thereby achieving side protection and aesthetic decoration of the board.
[0003] Traditional edge banding techniques have many unavoidable technical drawbacks: Firstly, hot melt adhesives contain harmful components such as formaldehyde and volatile organic compounds, which are continuously released during furniture use, polluting the indoor environment and failing to meet the health requirements for high-end environmentally friendly furniture and children's furniture. Secondly, the edge banding strip is bonded to the board with an adhesive layer. The adhesive layer is easily affected by changes in temperature and humidity, which can cause aging, cracking, and delamination, leading to the edge banding strip falling off and curling up, significantly shortening the lifespan of the furniture and resulting in extremely high after-sales rework costs. Third, the edge banding strip and the board surface have color differences and glue seams, resulting in poor overall appearance and unsatisfactory decorative effect; Fourth, traditional adhesive sealing processes have strict requirements for temperature, pressure, and adhesive uniformity, resulting in low production tolerance and easy occurrence of sealing defects.
[0004] Although there have been attempts in the industry to use single-coat edge sealing with paint, these methods only involve a single application of ordinary paint, which results in problems such as poor adhesion, easy delamination and peeling, low hardness, and poor wear and water resistance. They cannot replace the protective and decorative functions of traditional edge sealing strips, and the core issues of environmental protection and edge sealing firmness have not been resolved, making industrial-scale mass production impractical. Summary of the Invention
[0005] The purpose of this invention is to provide a UV-cured edge banding process for strengthening the edge banding of household panels based on chemical adhesives, so as to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a UV-cured edge banding process for strengthening the edge banding of furniture panels using chemical adhesives, comprising the following steps: Step 1: Pre-treat the sides of the board to expose wood fibers rich in active hydroxyl groups on the side surface; Step 2: Apply a UV-curable primer resin containing a chemical anchoring component system to the pretreated side, wherein the chemical anchoring component system contains at least two anchoring precursors with different chemical reaction mechanisms. Step 3: After coating, the material first undergoes a dark zone dwell stage. During this stage, the first anchoring precursor in the chemical anchoring component system pre-establishes a first covalent bonded anchoring layer on the side surface of the board through a chemical reaction with the hydroxyl groups of the wood. Step 4: After the dark area stay is completed, ultraviolet light irradiation is carried out. During the ultraviolet light irradiation stage, the second anchoring precursor in the chemical anchoring component system generates a second covalent bond with the wood fiber under the action of ultraviolet light. At the same time, the base coating resin undergoes photopolymerization cross-linking and curing to form a base coating curing layer that achieves chemical bonding with the side of the board through multiple covalent bonding types. Step 5: Apply UV-curable topcoat resin to the primer curing layer, and then cure it again with UV light to form a sealing surface layer; The chemical anchoring component system can construct a multi-point anchoring network containing at least two different covalent bonding types between the edge banding layer and the side of the board. In the multi-point anchoring network, the first anchoring method is established through a chemical reaction with the hydroxyl groups of wood in the dark area stage before ultraviolet light irradiation, and the second anchoring method is established during ultraviolet light irradiation.
[0007] Preferably, the first anchoring precursor is a polyurethane acrylate containing isocyanate groups. During the dark zone dwell stage in step 3, it undergoes a nucleophilic addition reaction with the hydroxyl groups of wood cellulose molecules to form a urethane bond for covalent anchoring. This is the covalent bond established by the first anchoring method.
[0008] Preferably, the second anchoring precursor is a combination of a hydrogen-abstracting photoinitiator and a hydrogen donor. In the ultraviolet irradiation stage of step 4, the excited-state hydrogen-abstracting photoinitiator abstracts hydrogen atoms from the α-carbon of the hydroxyl group of the wood cellulose molecule, generating free radical grafting sites on the wood surface. These sites initiate the grafting polymerization of acrylate double bonds in the resin, forming carbon-carbon covalent graft bonds. This is the covalent bond established by the second anchoring method.
[0009] Preferably, the isocyanate-containing polyurethane acrylate and the hydrogen-abstracting photoinitiator or hydrogen donor are coexisted in the same primer resin and coated in one step; during the dark zone dwell stage, urethane bond anchoring preferentially occurs, and during the ultraviolet light irradiation stage, hydrogen-abstracting graft anchoring and resin photopolymerization crosslinking occur simultaneously, thereby establishing two covalent anchoring layers with different chemical reaction mechanisms in the same process cycle.
[0010] Preferably, the hydrogen-abstracting photoinitiator is benzophenone or its phenyl-substituted derivative, and the hydrogen donor is a tertiary amine active amine; the primer resin also contains dibutyltin dilaurate as a catalyst for the reaction of NCO and OH; the duration of the dark zone dwell stage is 30-120 seconds, and the relative humidity of the environment is controlled below 50%.
[0011] Preferably, the chemical anchoring component system includes a hydrolyzable silane coupling agent containing unsaturated double bonds as one of the anchoring precursors. After coating, the silanols generated by hydrolysis condense with wood hydroxyl groups to form Si-O-wood covalent bonds. The unsaturated double bonds participate in the free radical copolymerization and crosslinking of the resin during the ultraviolet irradiation stage. The silane coupling agent establishes covalent anchoring during the dark zone residence stage and / or the ultraviolet irradiation stage. The silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane, which is directly added to the primer resin as one of the components of the chemical anchoring component system, with an amount of 1-5% by weight of the total resin mass.
[0012] Preferably, in step 3, before the dark zone dwell stage, the pretreated board side is further subjected to infrared preheating to remove surface adsorbed water, so that the moisture content of the board side is controlled to the range of 8-12%, so as to take into account the sensitivity of the isocyanate-containing anchoring precursor to moisture and the requirement of silanol condensation reaction for interfacial water molecules.
[0013] Preferably, in step 4, the ultraviolet light irradiation is a low-energy pre-curing process (200-400 mJ / cm²). 2 This allows the primer resin surface to partially cure and retain unreacted double bonds; In step 5, ultraviolet light irradiation is used for high-energy final curing (1000-1200 mJ / cm). 2 Through graded curing energy, the residual double bonds in the primer curing layer and the topcoat resin undergo interlayer copolymerization during the final curing stage, forming interlayer chemical bonds.
[0014] Preferably, the integrated primer curing layer and the edge sealing layer together constitute a gradient elastic modulus edge sealing structure: the primer curing layer is an elastic stress buffer layer with an elastic modulus of 1-20 MPa, and is covalently bonded to the side of the board through the multi-point anchoring network, enabling it to deform synchronously with the board's shrinkage and expansion due to moisture; the edge sealing layer is a hard topcoat layer with an elastic modulus ≥1 GPa; a gradient transition layer with an elastic modulus of 50-500 MPa is also provided between the elastic stress buffer layer and the hard topcoat layer; both the gradient transition layer and the hard topcoat layer are coated and cured layer by layer with ultraviolet light-curing resin.
[0015] Preferably, this process is applicable to the edges of sheet materials with any geometric configuration and to sheet material substrates of any material; The geometric configurations include straight edges, right-angled edges, rounded edges, and irregular irregular edges; The substrate material of the board is selected from wood, inorganic non-metallic materials, metallic materials or composite materials, especially aluminum honeycomb panels.
[0016] Preferably, the elastic stress buffer layer, gradient transition layer and hard topcoat layer are formed by layer-by-layer coating-pre-curing-final co-deep curing. The interfaces of adjacent layers copolymerize in the final curing stage through the unreacted double bonds retained in their respective pre-curing stages to form interlayer chemical bond connections, making the entire sealing layer a gradient integrated structure without interlayer physical interfaces.
[0017] This invention also discloses a formaldehyde-free and edge-sealing strip-free UV-curable furniture board edge-sealing structure, including a furniture board body, wherein an integrated edge-sealing layer is fixedly disposed on the side of the furniture board body; the integrated edge-sealing layer consists of a UV primer curing layer, a UV gradient transition layer, and a UV topcoat curing layer from the inside to the outside. The UV primer curing layer adheres tightly to the side surface of the furniture board body, with a thickness ranging from 0.15 to 0.25 mm. It is made of formaldehyde-free, high-adhesion UV-curable resin cured by ultraviolet light. The UV topcoat curing layer is tightly bonded to the outer surface of the UV base coat curing layer, with a thickness ranging from 0.25 to 0.35 mm. It is made of formaldehyde-free, high-wear-resistant UV-curable resin and cured by ultraviolet light. The UV gradient transition layer is located between the UV primer curing layer and the UV topcoat curing layer. The thickness of the UV gradient transition layer is determined by the thickness of the UV primer curing layer and the UV topcoat curing layer. For example, if the UV primer curing layer is 0.25 mm thick and the UV topcoat curing layer is 0.35 mm thick after UV curing, no UV gradient transition layer will be formed. If the UV primer curing layer is 0.15 mm thick and the UV topcoat curing layer is 0.25 mm thick, the thickness of the UV gradient transition layer will be 0.2 mm. The optimal curing parameters are: UV primer curing layer thickness 0.2 mm, UV topcoat curing layer thickness 0.3 mm, and UV gradient transition layer thickness 0.1 mm.
[0018] The integrated edge banding layer is bonded to the furniture board body at the molecular level, with no adhesive layer, no edge banding strip, and no gaps. The overall structure is solid and the surface is flat and smooth.
[0019] Furthermore, the process of this invention is highly versatile, applicable not only to traditional wood-based panels (such as solid wood, MDF, particleboard, etc.) but also to inorganic panels (such as fireproof boards, sintered stone), metal panels (such as aluminum plates, steel plates), and composite materials (such as aluminum honeycomb panels, wood-plastic composite panels, PVC panels). In terms of edge shape, in addition to straight edges, it can perfectly handle 90° right-angled corners, rounded corners with radius R1-R100mm, and various irregular and irregular edges such as door panel handle grooves, concave and convex edges, and stepped edges. This allows the invention to uniformly solve the edge banding problem for all types of furniture panels, possessing extremely high industrial application value.
[0020] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, the board and the edge banding layer are bonded by covalent bonds, resulting in a peel strength 3-5 times higher than traditional physical adsorption. The water immersion peel rate is reduced to below 2%, achieving a long-term stable and firm bond, significantly reducing the risk of detachment. Formaldehyde-free UV resin is used, making it environmentally friendly and healthy. When combined with a gradient modulus structure, the chemically anchored elastic buffer layer can deform synchronously with the wood's shrinkage and expansion, effectively absorbing stress, preventing cracking of the hard surface layer, and greatly extending the edge banding's lifespan.
[0021] 2. In this invention, UV resin is cured in seconds by ultraviolet light irradiation, without waiting for drying. The production efficiency is increased by more than 50% compared with the traditional edge banding process, saving the cost of edge banding strips, reducing material costs, and significantly reducing rework rate. Moreover, the process is simple and easy to implement: it is compatible with fully automatic and semi-automatic production equipment, the process parameters are stable and controllable, no complicated operation is required, it is suitable for edge banding of various types of panel furniture boards, and can directly realize industrial mass production.
[0022] 3. The edge sealing structure of the present invention has no adhesive layer, no edge sealing strip, and no gaps, resulting in a solid overall structure and a smooth and flat surface. Attached Figure Description
[0023] Figure 1 This is a flowchart illustrating the process flow of the UV-cured edge banding process for chemically bonded reinforced edge banding of household panels according to the present invention. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] The UV-cured edge banding process for strengthening panel edge banding in home furnishings based on chemical bonding includes the following steps: (1) Pre-treatment of the sides of the board to remove burrs and dust, so that the sides of the board are rich in active hydroxyl groups; (2) Apply a chemical anchoring component to the side of the pretreated board. The chemical anchoring component contains a first reactive group that can covalently react with the hydroxyl groups on the wood surface, and a second reactive group that can participate in ultraviolet light free radical polymerization. (3) After applying the chemical anchoring component, apply the UV-curable resin and cure it by UV irradiation to form an integrated edge sealing layer; In step (2), the first reactive group forms a covalent bond with the hydroxyl group of the wood; during the curing process in step (3), the second reactive group undergoes copolymerization and crosslinking with the UV-curable resin, thereby anchoring the edge sealing layer to the side of the board through chemical bonds.
[0026] The chemical anchoring component can be applied alone as a pretreatment agent or it can be included in the UV-curable primer resin for coating. When the chemical anchoring component is included in the primer resin, steps (2) and (3) are combined as follows: apply UV-curable primer resin containing the chemical anchoring component, and before or during UV irradiation, allow the chemical anchoring component to complete the bonding reaction with the hydroxyl groups of the wood, and then cure with UV to form a primer curing layer; then apply the topcoat resin and cure.
[0027] The chemical anchoring component is preferably selected from at least one of the following systems: (A) Polyurethane acrylate containing isocyanate groups, wherein the isocyanate groups act as the first reactive groups to form urethane bonds with the hydroxyl groups of wood, and the acrylate double bonds act as the second reactive groups to participate in ultraviolet curing. (B) Silane coupling agent, whose hydrolyzable group condenses with wood hydroxyl groups after hydrolysis to form Si-O-wood bond as the first reactive group, and contains acryloyloxy or methacryloyloxy as the second reactive group. (C) The combination of hydrogen-abstracting photoinitiator and hydrogen donor, under ultraviolet light irradiation, the excited state photoinitiator abstracts hydrogen atoms from the wood cellulose molecules, generating free radical sites on the wood surface as the first reactive group, while the acrylate double bond in the resin acts as the second reactive group to achieve graft crosslinking.
[0028] To achieve superior stress buffering, the primer curing layer or the entire edge banding layer can employ a gradient elastic modulus structure: from the inside out, it consists of an elastic stress buffer layer, a gradient transition layer, and a hard topcoat layer. The elastic stress buffer layer contains the aforementioned chemical anchoring components, tightly anchored to the board surface through chemical bonds, with an elastic modulus of 1-20 MPa, allowing it to deform synchronously with the wood. The outer hard topcoat layer has an elastic modulus ≥1 GPa, providing surface protection. Chemical anchoring ensures that the elastic layer does not peel off from the board during repeated tension and compression, thus making the gradient structure truly effective.
[0029] Example 1: Isocyanate-hydroxyl coupling chemical anchoring process (1) The sides of the board are sanded and high-pressure dusted to expose fresh wood fibers, and the surface adsorbed water is removed by infrared preheating to 60°C.
[0030] (2) Preparation of primer resin containing NCO-based polyurethane acrylate: 55 parts of isocyanate-based dual-curing polyurethane acrylate, 15 parts of hyperbranched polyhydroxy polyurethane, 8 parts of HEMA, 15 parts of HDDA, 5 parts of TMPTA, 0.1 parts of DBTDL, and 3 parts of photoinitiator Darocur 1173.
[0031] (3) Apply the above-mentioned primer resin to the side roller with a thickness of 0.2 mm. After coating, the board is conveyed through the dark zone for 90 seconds to allow NCO to react with the -OH of the wood to form urethane bonds for anchoring.
[0032] (4) First UV irradiation (365nm, 200mJ / cm) 2 (3 seconds) to allow the primer surface to partially cure.
[0033] (5) Roller coating of NCO-free hard UV topcoat resin (mainly epoxy acrylate) with a thickness of 0.3 mm.
[0034] (6) Second UV irradiation (365nm, 1000mJ / cm) 2 Full-layer curing (6 seconds). FTIR at the interface between the resulting edge banding layer and the substrate was detected at 1540 cm⁻¹. -1 The characteristic peak of urethane bond indicates that the peel strength is 4.2 times that of traditional UV edge sealing.
[0035] Example 2: Silane Coupling Agent Bridging and Anchoring Process (1) The pretreatment of the side of the board is the same as in Example 1.
[0036] (2) Prepare KH570 hydrolysate: 20g KH570, 72g ethanol, 8g water, 0.5g glacial acetic acid, stir at room temperature for 30 minutes to hydrolyze.
[0037] (3) Wipe the hydrolysate evenly onto the side of the board, with a wet coating amount of approximately 200g / m². 2 Let it air dry at room temperature for 10 minutes to allow the silanol groups to condense with the wood hydroxyl groups to form Si-O-wood bonds.
[0038] (4) Roller coating of UV primer resin (polyurethane acrylate, containing photoinitiator TPO 3%), thickness 0.2mm.
[0039] (5) UV irradiation (365nm, 1000mJ / cm) 2 The primer cures in 4 seconds, at which point the C=C double bonds of KH570 co-crosslink with the resin.
[0040] (6) Roller-coating and curing were performed as in Example 1. XPS analysis confirmed the presence of Si on the wood side, indicating that the damage occurred inside the resin rather than at the interface.
[0041] Example 3: Surface grafting and anchoring process for hydrogen-abstracting photoinitiators (1) The pretreatment of the side of the board is the same as in Example 1.
[0042] (2) Prepare a primer resin containing a type II photoinitiator system: 40 parts epoxy acrylate, 40 parts polyurethane acrylate, 10 parts HDDA, 3 parts benzophenone (BP), 5 parts active amine (N-methyldiethanolamine), and the remainder TMPTA.
[0043] (3) Roller coating of primer resin, 0.2 mm thick, direct UV irradiation (365 nm, 1000 mJ / cm). 2 (4 seconds). UV light excites BP, which abstracts hydrogen from the α-position of the hydroxyl group in wood cellulose to generate free radical sites. At the same time, it initiates cross-linking of acrylate with hydrogen donated by an active amine, forming a chemical graft layer on the wood surface.
[0044] (4) Roller-coating and curing. Adhesion tests showed that the peel strength of the grafted system was 60% higher than that of the control group using only type I initiator.
[0045] Example 4: Isocyanate-hydrogen abstraction dual-anchoring synergistic process This embodiment demonstrates the simultaneous introduction of isocyanate-containing polyurethane acrylate (first anchoring precursor) and hydrogen-abstracting photoinitiator or hydrogen donor system (second anchoring precursor) into the same primer resin, and the sequential establishment of a dual covalent anchoring network of urethane bonds and carbon-carbon graft bonds through time-controlled (dark zone stay + UV irradiation).
[0046] (1) Pretreatment of the side edges of the sheet material Same as Example 1: The sides of the board are sanded and high-pressure dusted to expose fresh wood fibers, and then preheated to 60°C with infrared to remove surface adsorbed water and adjust the moisture content to about 10%.
[0047] (2) Preparation of the dual anchoring system primer resin Prepare UV-curable primer resin according to the following table of parts by weight: Table 1. Formula of Curing Primer Resin by Weight Parts
[0048] Preparation method: Add each component in sequence under light-protected conditions and stir until completely dissolved and homogeneous. Avoid premature contact with moisture.
[0049] (3) Coating and Dark Area Retention The aforementioned primer resin was uniformly coated onto the sides of the board using a roller coating method, with the coating thickness controlled at 0.20 mm. After coating, the board immediately entered the dark conveying section, where it remained for 90 seconds, and the relative humidity was controlled below 45%. During this stage, -NCO undergoes a nucleophilic addition reaction with the hydroxyl groups on the surface of the wood fibers to form urethane bonds (-NH-COO-wood), establishing the first covalent anchorage.
[0050] (4) UV pre-curing (semi-curing) After the dark zone period, the first UV irradiation was performed: a high-pressure mercury lamp (365nm) was used, with an irradiation energy of 300 mJ / cm². 2 The duration is approximately 4 seconds. During this phase: Excited benzophenone abstracts a hydrogen atom from the α-carbon of the hydroxyl group in wood cellulose molecules, generating free radical grafting sites on the wood surface; This site initiates the graft polymerization of acrylate double bonds in the resin, forming carbon-carbon covalent graft bonds (secondary covalent anchoring). Meanwhile, the primer resin undergoes partial photopolymerization and cross-linking, and the surface reaches a semi-cured state (still retaining some unreacted double bonds), with no significant shrinkage in coating thickness.
[0051] (5) Applying topcoat and final curing A hard UV topcoat resin (same as in Example 1, mainly epoxy acrylate, containing 5% nano-SiO2) was roller-coated onto the pre-cured primer surface to a thickness of 0.30 mm. Then, a second UV irradiation was performed: energy 1200 mJ / cm². 2 (365nm), time 8 seconds, to allow the residual double bonds in the primer to undergo interlayer copolymerization with the topcoat resin, while the topcoat is fully cured.
[0052] (6) Performance test results Table 2. Performance Test Table of Dual Anchoring Synergistic Technology
[0053] (7) Results Analysis This embodiment constructs a dual covalently bonded network by synergistically using isocyanate anchoring and hydrogen-abstraction graft anchoring in the same primer resin. Wherein: Isocyanate anchoring provides a foundation for initial wet adhesion and water resistance; Hydrogen-abstraction grafting anchoring provides hydrolysis-resistant, durable chemical bonds, which perform particularly well in high-humidity environments; The synergistic effect of the two increases the peel strength by 30-50% compared to a single anchoring system, reduces the water-resistant peel rate to below 1%, and shows no damage after wet heat cycling, fully verifying the superiority of the dual anchoring synergistic process.
[0054] Examples 1-4 above primarily illustrate the straight-edge sealing of wood-based panels (such as particleboard). However, the core mechanism of this invention is a multi-point anchoring network based on chemical bonding (such as urethane bonds, silicon-oxygen bonds, and carbon-carbon graft bonds), which is not dependent on a specific panel substrate or edge shape. This is achieved by adjusting the pretreatment method and the permeability of the primer resin. Therefore, this process is widely applicable to the following areas: Expanding the types of boards used: For wood-based boards such as MDF and plywood, the pretreatment step can remain sanding; for metal boards such as aluminum and steel plates, the pretreatment can be adjusted to chemical oxidation or coupling agent treatment to generate active groups (such as hydroxyl groups) that can react with anchoring precursors; for aluminum honeycomb panels and PVC panels, active sites can be exposed through physical grinding or plasma treatment. The isocyanate-based or silane coupling agent anchoring system in this invention can form effective covalent bonds with these treated surfaces.
[0055] Edge shape adaptation: This process uses roller coating or spray coating to apply the adhesive. The coating head can be designed to conform to the shape of the workpiece or a robot can be used for spraying. Therefore, it can be evenly coated on various irregular shapes such as right angles, square corners, rounded edges with radius R1-R100mm, irregular notches, and handle grooves. The UV curing lamp can also be irradiated from multiple angles to match the shape of the workpiece to ensure complete curing of the coating.
[0056] For example, when sealing the right-angle edges of an aluminum honeycomb panel, the aluminum layer is first subjected to anodizing pretreatment to generate hydroxyl groups. Then, the dual-anchoring system primer resin in Example 4 is used. The dark area stays to form Al-O-urethane bonds. After UV irradiation, a dense coating is formed, and the peel strength can reach more than 2.5 N / mm.
[0057] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A UV-cured edge banding process for strengthening the edge banding of furniture panels using chemical adhesives, characterized in that, Includes the following steps: S1. Pre-treat the sides of the board to expose wood fibers rich in active hydroxyl groups on the side surface; S2. Apply a UV-curable primer resin containing a chemical anchoring component system to the pretreated side, wherein the chemical anchoring component system contains at least two anchoring precursors with different chemical reaction mechanisms. S3. After coating, the material first undergoes a dark zone dwell stage, so that the first anchoring precursor in the chemical anchoring component system forms a first covalent bonded anchoring layer on the side surface of the plate. S4. After the dark zone stay is completed, ultraviolet light irradiation is performed. The ultraviolet light irradiation promotes the second anchoring precursor in the chemical anchoring component system to form a second covalent bond with the wood fiber. At the same time, the base coating resin undergoes photopolymerization cross-linking and curing to form a base coating curing layer that is chemically bonded to the side of the board through various covalent bond types. S5. Apply UV-curable topcoat resin to the primer curing layer and cure it again with UV light to form a sealing surface layer. The chemical anchoring component system is used to construct a multi-point anchoring network between the edge banding layer and the side of the board, which includes at least two different covalent bonding types. In the multi-point anchoring network, the first anchoring method is established in the dark area stage before ultraviolet light irradiation, and the second anchoring method is established during ultraviolet light irradiation.
2. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical adhesive as described in claim 1, characterized in that: The first anchoring precursor is a polyurethane acrylate containing isocyanate groups, which is used to form urethane bonds with wood fibers for covalent anchoring during the dark zone dwell stage in step S3. The second anchoring precursor is a combination of a hydrogen-abstracting photoinitiator and a hydrogen donor, used to generate grafting sites on the wood surface during the ultraviolet irradiation stage in step S4, and to initiate the grafting polymerization of acrylate double bonds in the resin to form carbon-carbon covalent grafting bonds.
3. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical adhesive as described in claim 2, characterized in that: The isocyanate-containing polyurethane acrylate and the hydrogen-abstracting photoinitiator or hydrogen donor are coexisted in the same primer resin and coated in one step; during the dark zone dwell stage, urethane bonds are formed for anchoring, and during the ultraviolet light irradiation stage, hydrogen-abstracting graft anchoring and resin photopolymerization crosslinking are formed simultaneously.
4. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical adhesive as described in claim 3, characterized in that: The hydrogen-abstracting photoinitiator is benzophenone or its phenyl-substituted derivative, and the hydrogen donor is a tertiary amine active amine; the primer resin also contains dibutyltin dilaurate; the duration of the dark zone dwell stage is 30-120 seconds, and the relative humidity of the environment is controlled below 50%.
5. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical bonding according to claim 1, characterized in that: The chemical anchoring component system contains a hydrolyzable silane coupling agent with unsaturated double bonds, which is used to form Si-O-wood covalent bonds with the hydroxyl groups of wood after coating. Its unsaturated double bonds participate in the free radical copolymerization crosslinking of the resin during the ultraviolet irradiation stage. The silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane, which is added directly to the primer resin at a weight percentage of 1-5% of the total resin mass.
6. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical adhesive as described in claim 1, characterized in that: Before the dark zone dwell stage in step S3, the side of the pretreated board is preheated with infrared light to remove adsorbed water from the surface, so that the moisture content of the side of the board is adjusted to 8-12%. In step S4, the ultraviolet light irradiation has an energy of 200-400 mJ / cm². 2 The low-energy pre-curing process allows the primer resin surface to be semi-cured and retains unreacted double bonds. In step S5, the ultraviolet light irradiation has an energy of 1000-1200 mJ / cm². 2 High-energy final curing; through staged curing, the residual double bonds in the primer curing layer and the topcoat resin undergo interlayer copolymerization during the final curing stage, forming interlayer chemical bond connections.
7. The UV-cured edge banding process for chemically bonded reinforced edge banding of household panels according to any one of claims 1 to 6, characterized in that, The primer curing layer and the edge sealing layer together constitute a gradient elastic modulus edge sealing structure: The primer curing layer is an elastic stress buffer layer with an elastic modulus of 1-20MPa and a thickness in the range of 0.15-0.25mm. It is covalently bonded to the side of the board through the multi-point anchoring network and can deform synchronously with the board's shrinkage and expansion due to dryness and moisture. The edge sealing layer is a hard topcoat layer with a thickness in the range of 0.25-0.35mm and an elastic modulus ≥1GPa; A gradient transition layer with an elastic modulus of 50-500 MPa is also provided between the elastic stress buffer layer and the hard topcoat layer. Both the gradient transition layer and the hard topcoat layer are coated and cured layer by layer with ultraviolet light-curing resin.
8. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical bonding according to claim 7, characterized in that: The elastic stress buffer layer, gradient transition layer and hard topcoat layer are formed by layer-by-layer coating-pre-curing-final co-deep curing. The interfaces of adjacent layers copolymerize in the final curing stage through the unreacted double bonds retained in their respective pre-curing stages to form interlayer chemical bond connections, making the entire edge sealing layer a gradient integrated structure without interlayer physical interfaces.
9. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical bonding according to claim 1, characterized in that: Applicable to the edges of sheet materials with any geometric configuration and sheet substrates of any material; The geometric configurations include straight edges, right-angled edges, rounded edges, and irregular irregular edges; The substrate material of the board is selected from one of the following: wood, inorganic non-metallic materials, metallic materials, or composite materials.
10. The UV-cured edge banding process for strengthening furniture panel edge banding based on chemical bonding according to claim 9, characterized in that: The composite material is an aluminum honeycomb panel.